THE REQUIRED COMPETENCIES OF PROJECT MANAGERS IN METALLURGICAL COMPANIES IN THE CZECH REPUBLIC - Košťálová, Jana; Bednaříková, Marie; Paták, Michal (My University, 2018)
This paper is focussed on the problems of competencies of project managers in the corporate practice of metallurgical companies in the Czech Republic. The authors aim to assess the requirements imposed on the position of a project manager from the point of view of the corporate management. The authors identify the basic areas playing a significant role in assessment of project managers' competencies. They represent procedures applicable within selection of a project manager. Subsequently, the authors present outcomes of a survey, these outcomes show requirements of corporate management represented by human resource department managers of metallurgical companies in the Czech Republic when recruiting project managers in practice.
požadavované kompetence projektových manažerů v metalurgických firmách v České republice
Keywords: metallurgical companies; project management; project manager competencies; Czech Republic; metalurgické firmy; projektové řízení; kompetence projektových manažerů; Česká republika